2019
DOI: 10.1080/15284336.2019.1589232
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of elvitegravir/cobicistat/emtricitabine/tenofovir alafenamide in Asian participants with human immunodeficiency virus 1 infection: A sub-analysis of phase 3 clinical trials

Abstract: Background: The efficacy and safety of a single tablet regimen (STR) of elvitegravir/cobicistat/emtricitabine/ tenofovir alafenamide (E/C/F/TAF) was analyzed in Phase 3 clinical trials in antiretroviral therapy (ART)-naive and ART-experienced Asian participants infected with human immunodeficiency virus (HIV)-1 through 96 or 144 weeks. Objective: In Asian population requiring treatment, it is imperative to have data specific to this group, particularly as there is a general concern that Asians with lower body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Our study enrolled HIV/AIDS patients who underwent abdominal surgery. Of the HIV/AIDS patients on ART, most (32/35) achieved virologic suppression prior to surgery, which is roughly in line with other studies [23]. Thirty out of 64 patients did not choose ABT during the perioperative period, partly because ABT is not free in our health system.…”
Section: Discussionsupporting
confidence: 87%
“…Our study enrolled HIV/AIDS patients who underwent abdominal surgery. Of the HIV/AIDS patients on ART, most (32/35) achieved virologic suppression prior to surgery, which is roughly in line with other studies [23]. Thirty out of 64 patients did not choose ABT during the perioperative period, partly because ABT is not free in our health system.…”
Section: Discussionsupporting
confidence: 87%
“…Patients of Asian origin accounted for approximately 5-6% of the study population [11]. Considering such under-representation, data regarding the effectiveness of switching from TDF to TAF on reducing renal and bone toxicities in Asian patients with HIV infections remain scarce [12]. Further studies are needed to adequately inform HIV treatment in Asian populations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent pooled analysis of 26 trials showed the renal safety of TAF over TDF by examining a total of 12,519 person-years of exposure to TAF; there were no cases of proximal renal tubulopathy or Fanconi syndrome, and significantly fewer discontinuations due to renal adverse events in the TAF group than the TDF group (51). A sub-analysis of phase 3 clinical trials, which investigated efficacy and safety of elvitegravir/cobicistat/emcticitabine/TAF extracted the data of Asians and showed comparable efficacy and safety data between Asians and non-Asians (56). TAF is included as one of the components of the preferred ART regimens in the treatment guidelines in many high income countries (5,48,57,58).…”
Section: Tenofovir Alafenamidementioning
confidence: 99%